Basel Long COVID Cohort Study (BALCoS): protocol of a prospective cohort study - Andrea Meienberg; Michael Mayr; Rainer Schaefert; Gunther Meinlschmidt; Stefan Rohner; Rebekka Schnepper; Katrin Bopp (BMJ Open)
Introduction The recent pandemic caused by SARS-CoV-2 had a profound global impact. While many individuals recovered from COVID-19, some developed long-lasting symptoms that significantly disrupted daily life. The WHO defines this condition as post-COVID-19 condition (PCC). Common symptoms include fatigue, dyspnoea, sleep disturbances and cognitive difficulties. Increasing evidence suggests that PCC is a multifactorial condition, shaped not only by biomedical but also psychological and social factors. This article presents the protocol of the Basel Long COVID Cohort Study (BALCoS), which aims to improve understanding of PCC by capturing clinical, functional and psychosocial aspects through repeated assessments over the course of 1 year.Methods and analysis BALCoS is a prospective, single-site cohort study. Inclusion criteria include either a probable or confirmed history of SARS-CoV-2 infection with persistent symptoms consistent with the WHO definition of PCC, sufficient German language skills and age ≥18 years. At baseline, we collected detailed information on previous SARS-CoV-2 infections, symptom history, reinfections, COVID-19 vaccination status and pre-existing medical conditions. The study includes standardised psychometric assessments, physical performance tests, ecological momentary assessments (EMAs), neurocognitive testing and blood sample collection. Assessments are scheduled at baseline and at 3-month, 6-month and 12-month follow-up. All participants complete psychometric assessments at each time point. Blood samples are only collected at baseline. Neurocognitive testing and physical performance measures are collected at baseline and 12-month follow-up for in-person participants only. Participants who are unable to attend in person complete a remote version of the study, excluding these in-clinic assessments. EMAs are initiated the day after each time point and consist of eight questions over 10 consecutive days. The study is exploratory in nature, with a target sample size of 120 participants. BALCoS is part of the Horizon Europe Long COVID project, a multinational interdisciplinary research consortium integrating mechanistic, clinical and interventional studies.Ethics and dissemination The study was approved by the Ethics Commission of Northwest and Central Switzerland (BASEC-ID: 2023–00359) and is registered at ClinicalTrials.gov (ID: NCT05781893). All participants provide written informed consent. Study findings will be disseminated through peer-reviewed publications.Trial registeration number NCT05781893.